When the wind was a river : Aleut evacuation in World War II - Kohlhoff, Dean (Univ. of Washington Press, 1995)
World War II came to the North Pacific in June 1942. Alaska's Native people living on the Aleutian and Pribilof islands, the Aleuts, felt its impact as did no other American citizens in that region. Forty-two residents of Attu Island were captured and imprisoned in Japan and, in response to Japanese bombings of Dutch Harbor and invasions of Kiska Island, the American military evacuated the remaining 881 Aleuts from the islands to camps in southeastern Alaska. The story of the removal of the Aleuts is little known outside Alaska. Dean Kohlhoff delved extensively into civilian and government archives, as well as videotapes of Aleuts chronicling their wartime experiences, to compile this engrossing account of the evacuation